Longitudinal Evaluation of Chicago's Community Policing Program, 1993-2001 - Skogan, Wesley G. ([Verlag nicht ermittelbar], 2002)
The purpose of this study was to evaluate the long-term organizational transition of the Chicago Police Department (CPD) to a community policing model. The Chicago Alternative Policing Strategy (CAPS) was an ambitious plan to reorganize the CPD, restructure its management, redefine its mission, and forge a new relationship between police and city residents. This evaluation of the CAPS program included surveys of police officers, residents, and program activists. In addition, observational data were collected from beat meetings, and aggregate business establishment and land-use data were added to describe the police beats and districts.